PATH-13. PLEOMORPHIC XANTHOASTROCYTOMA INTEGRATED GENOMIC CHARACTERIZATION - WHAT HAVE WE LEARNED?. (4th December 2020) - Vaubel, Rachael; Zschernack, Valentina; Caron, Alissa; Milosevic, Dragana; Jenkins, Robert; Kipp, Benjamin; Rodriguez, Fausto; Tran, Quynh; Orr, Brent; Pietsch, Torsten; Giannini, Caterina
Abstract: Pleomorphic xanthoastrocytoma (PXA) is a rare astrocytoma occurring predominantly in children and young adults. It is characterized histologically by large pleomorphic, spindled and lipidized cells with frequent eosinophilic granular bodies and pericellular reticulin deposition. BRAF p.V600E mutation and CKDN2A/B deletion are the most common genetic alterations. We report the integrated genomic characterization of a cohort of 67 patients (37 F, 30 M; median age 20.3 years (interquartile 13.4–32.9) with histologically defined PXA (52, 78%) or anaplastic PXA (A-PXA) (15, 22%), using genome-wide cytogenetic (ThermoFisher Oncoscan, n=67), methylation profiling (Illumina EPIC array, n=43), and targeted next generation sequencing (n=32). BRAF p.V600E mutation (n=51, 76.1%) and CDKN2A/B deletion (n=63; 94%) were the most frequent alterations. Of 16 BRAF p.V600E negative cases, 7 showed an alternative BRAF activating mutation (n=2), NF1 (n=3) mutation or ATG7-RAF1 fusion (n=2). Targeted TERT analysis found promoter mutations in 3 (of 58) cases, but TERT amplification was absent. Supervised and unsupervised methylation profiling against a comprehensive reference cohort demonstrated consensus grouping with the PXA class in 36 of 43 cases; while the minority grouped with a ganglioglioma class (n=3), with reactive brain or had no resolvable subgroup (n=4). Follow-up was available in 61 patients (91.0%) (median 63 months). Overall survival was significantly different between PXA and A-PXA (5-year:80.4% vs. 55.1%; p=0.001), but not progression-free survival (5-year:61.7% vs. 39.8%; p=0.128). Our data confirm the high frequency of MAP-K abnormalities and CDKN2A/B deletion in PXA. WHO grade remains a strong predictor of patient overall survival.